Leading procurement strategy driving value through the supply chain - Mena, Carlos; Hoek, Remko I. van; Christopher, Martin (Kogan Page, 2014)
"Leading Procurement Strategy shows how to unleash full business value through procurement. The book provides a broad perspective of different industries, underpinning academic theory and short case studies to help readers clearly understand the competitive advantage and impact of procurement. The authors tackle key issues that procurement practitioners encounter and offer the tools for managing procurement and supply. Their indispensable advice makes it easier to manage and mitigate risks in a supply chain and to appreciate the major issues affecting the procurement function"